Children and youth digital literature on tablets and smartphones: An opportunity to get new readers - García-Rodríguez, Araceli; Gómez-Díaz, Raquel (Anuario ThinkEPI, 2017)
The connectivity phenomenon and the expansion of smartphones and tablets are playing a major role among children and adolescents. One option for promoting reading is to positively align children and reading on digital devices. For that, it is necessary for all agents involved in the chain of book creation, diffusion, and consumption get involved. In addition, global strategies need to be established that describe the ideal conditions for reading development. This article presents actions that publishers, developers, mediators, and the Administration can do to reach this goal.
Keywords: Children and youth digital reading; Children and youth reading promotion; Digital reading promotion; Ereading.